Extraction of mimosine from dried leaves and defatted seed of Leucaena leucocephala and its biodiesel oxidative stability / Norfadhilah Ramli - Norfadhilah , Ramli (2019)
Leucaena leucocephala has long been recognized by human as one of the miracle tree with multifunctional benefits and uses. Due to its highly nutritious, palatable, widely available and drought tolerant characteristics, it has been regards as a good option for animal fodder. Animals feed with Leucaena leucocephala foliage had shown an increment in weight compared to other fodder choices. However, this tree contains a non-protein amino acid toxin known as mimosine. The detrimental effect of mimosine on animals such as alopecia, reduced in weight, and excessive saliva becomes a major drawback for farmers to incorporate Leucaena leucocephala in the animal’s diet. Works have been done to remove mimosine from Leucaena leucocephala leaves and seeds such as drying, soaking and even cloning. Despite its anti-nutritional characteristic, mimosine possesses antioxidative behaviour which could be utilised as biodiesel additives. Therefore, this study is carried out to seek an effective method in removing mimosine from Leucaena leucocephala leaves and seeds as well as its potential antioxidative properties in biodiesel oxidative stability. The study was initiated by determining the mimosine yield from local Leucaena leucocephala leaves and seeds using two different extraction methods; HCl digestion and Soxhlet extraction (SXE) with water as extraction solvent. The result showed SXE yielded higher mimosine extraction followed by HCl digestion method with 21.633 μg and 9.764 μg in seeds while 10.261 μg and7.2 μg per 100g dry mass in leaves respectively. Next, SXE method was employed to remove mimosine from seed meals (defatted seeds) after oil extraction process to investigate whether leftover seed meals still contain mimosine before being given to the animals. The result depicted defatted seeds (DS) score lower mimosine value with 8.150 μg compared to the undefatted seeds (UDS) which is 10.203 μg per 100g dry mass during first SXE cycle. However, the result was slightly reverse for mimosine content where the value was higher in DS compared to the UDS during the second cycle of SXE. The effect of heat also has been evaluated where UDS has higher mimosine concentration (24.5μg per 100g dry mass) compared to DS (19.417μg per 100g dry mass). Meanwhile, oxidative stability tests were conducted at a temperature of 110 °C and airflow of 10 L/h using a Rancimat machine with automatic induction period (IP) determination following the EN 14112 Method. The highest stabilization efficacy of mimosine was obtained at 10,000 ppm with IP 69.4 hours. For FRAP assay, UTS has higher FRAP value of 66.02 μmol compared to TS extracts with 55 μmol /Trolox equivalent (TE). Overall, SXE showed to be more effective in removing mimosine while heat plays a major role in reducing mimosine in seed meals. Whereas, antioxidative properties of mimosine showed a promising result to be used as a biodiesel additive.